Atributo de alma e coração praticado: a voz de Riva Bauzer na formação do adminitrador público (EBAP, 1965-1970) / Attribute of soul and practiced heart: the voice of Riva Bauzer in the formation of the public adminitrator (EBAP, 1965-1970) - Corrêa, Laura Henrique; Oliveira, Aline Lourenço de (Revista de História e Historiografia da Educação, 2020)
Este texto incide sobre a atuação feminina no período de implantação dos cursos de administração pública no Brasil. Para tanto, foram analisadas as publicações da Escola Brasileira de Administração Pública (EBAP) durante o período de produção do periódico – 1954 a 1977. Neles, a autora que mais publicou foi Riva Bauzer, com os títulos: formação para administração pública I (1965), II (1966), e III (1970); nos quais expõe abordagens educativas que integraram o processo de surgimento da experiência brasileira de formação do administrador público. Em seus registros se identifica a frequente preocupação com a elaboração de saberes locais, produzindo lacunas no discurso mais ratificado da época. Ao final é possível perceber um posicionamento efetivado na percepção do educando brasileiro, seu território e particularidades, entoado por uma ação educativa que esbanja clareza e arte: atributo de alma e coração praticado. *** This text focuses on women's activities during the implementation of public administration courses in Brazil. To this end, the publications of the Brazilian School of Public Administration (EBAP) were analyzed during the period of production of the journal - 1954 to 1977. In them, the author who most published was Riva Bauzer, with the titles: training for public administration I (1965), II (1966), and III (1970); in which it exposes educational approaches that integrated the process of elaborating the Brazilian experience of training public administrators. Its records identify the frequent concern with the elaboration of local knowledge, producing gaps in the most ratified discourse of the time. At the end, it is possible to perceive an effective positioning in the perception of Brazilian students, their territory and particularities, intoned by an educational action that oozes clarity and art: attribute of soul and practiced heart.